REDESAIN SISTEM SIRKULASI, PARKIR DAN RAMBU-RAMBU LANSKAP KAMPUS 1 UNIVERSITAS KRISTEN SATYA WACANA - Erik Kado Nugroho; Endang Pudjihartati; Bistok Hasioholan Simanjuntak (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2014)
Circulation, signage, and parking are important parts of planning and designing campus openspace landscape. This study aimed to redesign the circulation system, signage, and parking of the landscape of campus 1 Satya Wacana Christian University in order to resolve the prevailing problems. Analysis and synthesis (redesign) using the method of “Problem Solving” was applied by following these steps (1) inventories (primary and secondary data), (2) analysis, (3) synthesis, (4) planning, and (5) design. The results showed that the problem of circulation conflict between pedestrians and vehicle users will be overcame by adding pedestrian pathways which are tailored to user population. The lack of signages indicated that user’s navigation system was weak thus the campus open-space landscape required signpost and map. The illegal parking of four-wheeled vehicles caused disturbances in several spots of the open-space. This can be addressed by diversion of vehicles parked in a location that is available and assertion of parking or parking-ban signs. The material used in the process of redesigning the pedestrian pathways and signages applies design principles.